GETTING RE-CHARGE THE STUDENTS’CHARACTERS IN ENGLISH DAYS PROGRAM (EDP) - Iradatul Hasanah; Hayati Syafri (International Conference on Languages and Arts, 2014)
This paper is aimed to figure out the students’characters which are built through EDP in STAIN Bukittinggi. Nowadays, in the process of learning English, the lecturer needs to consider about how to encourage the students’ characters, not just teaching them English. However, the English students tend to spend their time instudying the theories, reading English textbooks, and writing the resumes but less practicing. In this case, EDP provides additional time for the students in practicing English. So, the lecturer also has more chances to activate the students’ characters. Simply put, the lecturer can give treatments to influence the students in having a better life. These kinds of treatments can be given by the lecturer through one of EDP’s activities that is giving weekly motivation. The lecturer then can encourage the students continuously to speak English all day long while educate them to be diligent and have a high willing to practice their English.Moreover, the lecturer also can re-charge the students’ responsibility and integrity in running the program because the lecturer gives them her belief in order the students can be honest, cared and respect each other in doing the program while keeping EDP’s rules.Finally the lecturer can emphasize both students’ characters andtheir speaking abilityby giving weekly motivation in English Days Program itself.   Keywords: Student characters, weekly motivation